THE TEACHER’S USE OF TRANSLATION IN ENGLISH LANGUAGE TEACHING BASED ON SCIENTIFIC APPROACH AT SMP NEGERI 4 AND SMP NEGERI 5 SINGARAJA - Ni Made Sumarningsih; Gede Batan; Luh Diah Surya Adnyani (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2018)
This study was conducted as an attempt to investigate in what step of scientific approach theteachers most frequently use translation in English Language Teaching as well as to find out the teachers’reasons toward the use of translation in English Language Teaching based on scientific approach atSMP Negeri 4 Singaraja and SMP Negeri 5 Singaraja. It was conducted in qualitative research design.There were two teachers chosen as the subjects of study. The data were collected through audio recordingthe teaching and learning process and interviewing the subjects of study, while the techniques ofanalyzing data were done descriptively following the four processes according to the theory of Miles &Huberman (1984), namely: data collection, data reduction, data display, and conclusion drawing. Theresults of analysis indicated that the teachers most frequently used translation in exploring step of scientificapproach. In addition, there were seven teachers’ reasons found in relation to the use of translationin the classroom, namely to help the students’ difficulty in: (1) understanding the instruction given bythe teacher, (2) understanding the English vocabulary, (3) asking something in English, (4) understandingthe tenses or grammar, (5) understanding the material deeply, (6) doing the task, and (7) presentingtheir work. The related parties interested in the same area of the research should give deeper concern indoing wider range of aspects involved in further study.Keywords : Translation, the Use of L1 in ELT, Scientific Approach